A Simulation and Analysis of Sustainable Accommodations: Exploring the Feasibility of Earthships in Cold Regions - Schulze Mönking, Clara Josefine; Schäfer, Stefan; Bisevac, Nikola (Engineering Science & Technology, 2025)
In this paper, the thermal performance of an Earthship in New Mexico, Finland, Germany, and Norway is simulated. After testing various design changes and their influence on thermal performance, a final Earthship model optimised for the Nordic climate is derived. The main findings are that an unheated greenhouse with large windows on the south side of the building stabilises the temperature in the living area and reduces energy consumption and that the wall between this greenhouse and the living area should be well insulated. Thermal mass stabilises the indoor temperature but can also lead to higher heating energy consumption. The results show that incorporating Earthship technology into conventional houses could help reduce their environmental impact and contribute to the green transition of the building sector.